STRATEGI BISNIS KOPI MEREK COFFESSO PT DAVID ROY INDONESIA - Cindya Rienaya; Mudatsir Najamuddin; Akhmad Mahbubi (Departement of Agribusiness Faculty of Science and Technology, 2017)
This study aims to determine suitable business strategies for PT. David Roy Indonesia. IFE matrices, EFE, SWOT, and QSPM were employed to analyze the data. Results from IFE matrices indicated that the company's main strength is the vision of company with a score of 0.486 and the main drawback is the location of the plant with a score of 0.280. In addition, results from EFE matrices indicated that the main opportunity is government policies related to the export of coffee beans with a score of 0.397, and the main threat is government policy related to the import of processed coffee with a score of 0.266. The SWOT analysis results several alternative strategies and QSP matrices indicated that resources differentiation strategy getting the highest priority of all